AB0289 Analysis of Joints Susceptible To Rheumatoid Arthritis (RA) and Their Recovery Sequence Based on DAS28 with Smart System of Disease Management (SSDM) in China: A Prospective Cohort Study. (15th July 2016) - Mu, R.; Yang, J.; Wang, H.; Xin, X.; Wei, H.; Zhang, F.; Li, X.; Dong, J.; Jia, Y.; Liu, Y.; Xiao, F.; Li, Z.
Abstract : Background: The disease activity score in 28 joints (DAS28) 1 and health assessment questionnaire (HAQ) 2 are guides the treatment of rheumatoid arthritis (RA). Smart System of Disease Management (SSDM) is a series of mobile phone applications for chronic diseases management, which includes interfaces of both doctors' and patients' applications. After entry data of lab test, treatment regiments, and executing DAS28 evaluation entry by patients, all data can be synchronized automatically to the authorized rheumatologist' mobile tool. The rheumatologist can adjust treatment regiments base on patients' profile. We have confirmed that the results of self-assessment in DAS28 by RA patients with SSDM were consistent with professionals' assessment in our previous study 3 . Objectives: To evaluate the susceptible joints and the recovery sequence of swollen joint counts (SJCs) and tender joint counts (TJCs) based on DAS28 which self-assessed by Chinese RA patients with SSDM, and to describe the association between DAS28 and HAQ. Methods: Since August 31, 2014, thirty-one rheumatologists from twenty-five hospitals participated in the study. Adult patients fulfilling the 1987 ACR (formerly the American Rheumatism Association) criteria for RA were recruited. Patients were taught to self-assess DAS28 and HAQ with SSDM at the baseline, and were asked to repeat the assessment once a month during the treatment. Results: As of January 14, 2016, 636 RA patients self-assessed for 2, 306 times. At the baseline, 1, 628 joints were swollen and 2, 761 joints were tender. The top five swollen joints were right wrist, right middle proximal interphalangeal, left wrist, right knee and left knee joints, and the top five tender joints were right wrist, left wrist, right knee, left knee and right shoulder joints. Table1 shows the proportion of different joint involvement at the baseline and the last assessment. After treatment, the top five recovery joints were left little metacarpophalangeal, left ring metacarpophalangeal, right index proximal interphalangeal, right little metacarpophalangeal and right middle proximal interphalangeal in tender, and left little proximal interphalangeal, left little metacarpophalangeal, right little proximal interphalangeal, right little metacarpophalangeal and left index proximal interphalangeal in swelling. HAQ score showed that the top two difficult functions of RA patients were "reaching" and "hygiene" at the baseline. At the last assessment, the degree of recovery about "hygiene", "dressing and grooming" function were quicker than "reaching" and "walking", which was matched with DAS28's joints recovery characteristic (Detailed see Table 2 ). Conclusions: In this study, most involved joints in tender and swelling are hand and wrist joints, which co-related to the physical activity function of "hygiene" and "dressing and grooming". After treatment, hand joints recovered more quickly than other joints, which matched with HAQ assessment results. References: J Rheumatol 1993; 20: 538–41. A&R 1983, 26(11):1346–1353 Arthritis Rheumatol. 2015; 67 (suppl 10). Disclosure of Interest: None declared